(3GdGdJRGe HGdEYdGe hGdJHUjQ aj GdJYGbO HGSJNOGe GdJbfjGJ GdMOjKI (B: s (3OQGSI ebGQfI (B/ s - (3YeGO MSf YHO GdYXje s; (3eMeO TcQj SQhQs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2015)
(3JfGhdJ aj gPg GdQSGdI GdGJj (B:- - (3eaghe GdJYGbO HGSJNOGe GdJbfjGJ GdMOjKI hPdc ef MjK eGgjI gPG GdYbO hNUGFUg hJejjRg Yf ZjQg ef GdYbhO GdGNQi GdeJTGHg eYg(B. - (3eGgjI GdGdJRGe HGdEYdGe CSGSg (B- (3TQhWg aj GdJYGbO HhSGFd GdcJQhfjI hGJVM dfG Cf eaghe gPG GdGdJRGe hWHjYJg (B- (3CSGSg (B- (3TQhWg aj gPG GdfhY ef GdJYGbO GNJda JeGekG Yf GdJYGbO GdJbdjOj(B. - (3CMcGe gPG GdGdJRGe ef MjK fWGbg hcjajI JfajP GdJGLQ GdGdcJQhfj ddGdJRGe HGdEYdGe YHQ THcI GdGfJQfJ hcjajI EKHGJg hGdLRGA GdeJQJH Ydj GNdGdg HgPG GdGdJRGe(B: (3hbO TedJ GdOQGSI gfG GdGdJRGe HUhQjJg(B. - (3OQGSI ebGQfI dYOO ef GdJhLjgGJ GdChQhHjI (B- (3GdJTQjYGJ GdaQfSjI hGdeUQjI (B- (3HYV JTQjYGJ GdOhd GdYQHjI eKd JhfS(B: (3GdCQOf(B: (3GdEeGQGJ hcPdc CjVkG HYV CMcGe Gdabg GdESdGej(B: (3ceG TedJ CjVG YOO ef GdCMcGe GdbVGFjI GdUGOQI ef GdeMGce GdaQfSjI hHYV GdCMcGe GdUGOQI ef eMceI GdbGgQI GdGbJUGOjI(B: (3HGdEVGaI Edj CMcGe eMceI GdfbV GdeUQjI(B. - (3HYV GdebJQMGJ GdJTQjYjI dJYOjd bGfhf MeGjI GdeSJgdc aj eUQ Qbe (B67 (3dSfI (B2006: (3heTQhY bGfhf GdJLGQI GdGdcJQhfjI GdeYO ef LGfH eQcR GdeYdheGJ hOYe GJNGP GdbQGQ GdJGHY deLdS GdhRQGA HGdEVGaI Gdj HYV GdJhUjGJ(B. s
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI, cdjI GdMbhb, bSe GdbGfhf GdeOfj (B2015.s
(3HHdjhLQGajG(B: (3UaMGJ (B322-344.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3EHQGe GdYbO GdEdcJQhfis; (3GdYbO GdEdcJQhfjs; (3GdEKHGJ GdEdcJQhfjs; (3GdEYdGe hGdJHUjQs; (3GdJYGbOGJs; (3GdJbfjGJ GdMOjKIs; (3GdJYGbO HhSGFd EdcJQhfjIs; (3GdeSJgdc GdEdcJQhfjs; (3JHUjQ GdeSJgdcs; (3GdJGLQ GdEdcJQhfjs; (3JejjR YbO GdHjY GdEdcJQhfjs; (3GdGdJRGe HGdEYdGes; (3GdEOdGA HGdeYdheGJ YHQ GdEfJQfJs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdeOfjs